Strategi Pengasuh PONPES dalam Menjaga Kesehatan Mental Santri di Ponpes Salafiyah Sentot Alibasya Kota Bengkulu - Nurul Falah; Alfauzan Amin; Nelly Marhayati (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2021)
This research uses a qualitative type with a descriptive approach. Data collection techniques use observation, interviews and documentation. Research informants included: Kyai Ponpes Salafiyah Sentot Alibasya, Pondok Caretaker, male students and female students. The data analysis technique uses the Narrative Analysis Technique which is carried out by collecting data describing events or occurrences and then compiling it into a story using a storyline. The results of this thesis research are: 1. The mental health of children at the Salafiyah Sentot Alibasya Bengkulu Islamic boarding school as a whole is not the same, but the system implemented by the Islamic boarding school to handle problems that arise is very good. Like the actions taken to deal with new students so that they are willing to open up and obey existing regulations, this cannot be separated from the role of the santri guardians who follow the development of the students through meetings held by the Islamic boarding school. 2. The strategy implemented by the Sentot Alibasya Bengkulu Salafiyah Islamic boarding school is appropriate to deal with the students with the problems they face. For students who violate the rules that have been set, the boarding school administrators are ready with the appropriate punishment to be given to the students. By holding dormitory cleaning activities, weekly activities every Friday night after the Maghrib prayer congregation, followed by reading Yasin and Tahlil and after that reading the Barzanji Prayers, the researchers saw that this was the right strategy for the students to be able to maintain their mental health. 3. Supporting factors for the mental health of students at the Salafiyah Sentot Alibasya Islamic boarding school can be seen from the readiness of the boarding school caregivers in handling any problems posed by the students, besides that, there is support from the guardians of the students for the progress of the Islamic boarding school. Meanwhile, the inhibiting factor in implementing the boarding school caregiver's strategy in maintaining the mental health of students lies in the various characters of the students, where not all students commit violations not only once but more than once and the factors that encourage them to commit these violations have various motives. Keywords: Strategy, Islamic Boarding School Caregivers, Mental Health